The Effectiveness of Swiss Ball Exercise to Increase Balance and Mobility of Patient with Stroke - Putra Agina Widyaswara Suwaryo; Eko Budi Santoso; Bambang Utoyo (Babali Nursing Research, 2023)
Stroke cases increased to 10.9% in 2018 or an estimated 2.1 million people. Central Java was ranked in the top 10 with 11.8% of stroke cases. Post-stroke control adherence to health care facilities nationally is also still low. The development of treatment methods for stroke patients has been very rapid in hospitals, starting from therapy, rehabilitation care and the results have shown a decrease in mortality due to stroke in the acute phase. The most effective method to improve balance and mobility of post-stroke patients is using Swiss Ball Exercise. The purpose of this study was to prove the effectiveness of Swiss ball exercise on the level of balance and mobility in post-stroke patients. This study used a quasi-experimental design with a pretest-posttest control group design, with a post-stroke patient population. The sample in this study was taken by consecutive sampling technique, with the inclusion criteria of acute post-stroke patients who experienced pharese or weakness of the upper and lower limbs for a duration of 1-3 months, aged 40-60 years, male and female patients, no disturbances. visual and sensory disturbances. Exclusion criteria were patients with spinal deformity, mental disorders, a history of spinal surgery, hemorrhagic stroke and cognitive deficits. The research sample amounted to 36 people who were divided into 2 groups. The first group got Swiss Ball Exercise in 35-40 minutes for 6 days/week once a day for 3 weeks. The results showed that the control group and the intervention group were 18 respondents respectively. Swissball exercises were carried out by respondents with the assistance of a facilitator for 6 times in 1 week and were carried out for 3 weeks, a total of 18 times. The results of statistical tests using the Wilcoxon test showed that there were significant changes in stroke patients, the majority of whom had non-hemorrhagic strokes. These changes were assessed using the Berg Balance Scale (p=0.005) and the Time Up Go Test (p=0.002) in the intervention group. Conclusion that swiss ball exercise is effective to improve balance and mobility of post-stroke patients